The Effect of Inquiry Based Learning Method in Enhancing Students’ Writing Ability in Narative Text at The Eight Grade Students of SMP Plus Ja’al Haq Kota Bengkulu - Meranti Injelia; M. Arif Rahman Hakim; Pebri Prandika Putra (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study aims to examine the effect of Inquiry-Based Learning (PBI) in improving the narrative writing ability of grade VII students at Ja'al Haq Plus Junior High School in Bengkulu City. Writing competence is an important element in English language learning; however, many students face challenges in organizing ideas, developing content, and applying appropriate language structures. This study used a quasi-experimental method involving two groups: an experimental group and a control group, each consisting of 10 students. The research procedure consisted of pre-test, treatment through the application of IBL for the experimental group, and post-test. Data were analyzed using paired t-test and independent sample t-test in SPSS 22. The findings showed that although both groups showed improvement in their writing scores, the experimental group showed a greater average improvement. Nevertheless, the independent t-test results showed no statistically significant difference (p = 0.591 > 0.05). Despite the limited statistical effect, IBL was shown to encourage students' engagement, creativity, and autonomy during the writing process. These results imply that, despite its minimal measurable impact, IBL remains a useful pedagogical approach to teaching writing in the junior high school context.